Antibiotic Use in Animals - Savic, Sara (IntechOpen, 2018)
The book Antibiotic Use in Animals has everything said in the title, but it is not only meant for the veterinarians. It is intended to be used also by the medical doctors, animal owners, consumers of food of animal origin, etc. The book has five sections: "Introduction," "Use of Antibiotics in Animals," "Antibiotics and Nutrition," "Probiotics," and "Antimicrobial Resistance." Each of the sections discusses about one side of the antibiotic usage. Each group of authors has dedicated their work to one of the topics with key roles of antibiotics in the health of animals and public health in general. This book is a work of scientists and researchers in the topic of antibiotic use, and with this book, we hope to open new questions and deepen the research on roles of antibiotics in everyday life.